2006
DOI: 10.1152/ajprenal.00500.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal cortical cyclooxygenase-2 expression in hyperfiltration in rats with high-protein intake

Abstract: Renal cortical cyclooxygenase-2 (COX-2) is restricted to the macula densa and adjacent cortical thick ascending limbs (MD/cTALH). Renal cortical COX-2 increases in response to diabetes and renal ablation, both of which are characterized by hyperfiltration and reduced NaCl delivery to the MD due to increased proximal NaCl reabsorption. High-protein intake also induces hyperfiltration and decreases NaCl delivery to the MD due to increased NaCl reabsorption proximally. We investigated whether high protein induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
4
23
3
Order By: Relevance
“…Although the beneficial effects of COX-2 inhibitors in these models of progressive glomerular injury likely are the result of multiple mechanisms, including inhibition of hyperfiltration (10,27), as well as direct anti-inflammatory effects (28), our studies indicate a potentially pathogenic role for COX-2 metabolites to increase the susceptibility of podocytes to further injury and therefore suggest that podocytes also might be a target for COX-2 inhibitors in progressive glomerular injury. In this regard, Kennedy et al (13) demonstrated that mechanical stretch induced expression of COX-2 and the EP4 subtype of prostaglandin E2 receptor in cultured podocytes, and in the stretched podocytes, prostaglandin E2 administration induced actin stress fiber dissociation.…”
Section: Discussionmentioning
confidence: 77%
“…Although the beneficial effects of COX-2 inhibitors in these models of progressive glomerular injury likely are the result of multiple mechanisms, including inhibition of hyperfiltration (10,27), as well as direct anti-inflammatory effects (28), our studies indicate a potentially pathogenic role for COX-2 metabolites to increase the susceptibility of podocytes to further injury and therefore suggest that podocytes also might be a target for COX-2 inhibitors in progressive glomerular injury. In this regard, Kennedy et al (13) demonstrated that mechanical stretch induced expression of COX-2 and the EP4 subtype of prostaglandin E2 receptor in cultured podocytes, and in the stretched podocytes, prostaglandin E2 administration induced actin stress fiber dissociation.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, COX2 inhibition decreases renal hyperfiltration, proteinuria, and glomerulosclerosis in a variety of animal models (28 -30). These effects are thought to be due to COX2 inhibition-mediated reductions in vasodilatory prostaglandins, such as prostacyclin and PGE (30), leading to decreased intraglomerular capillary pressure. Some data support the hypothesis that COX2-derived prostaglandins exert vasodilatory actions at the renal arteriolar level in animals and humans (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that there are important sex-dependent differences in the evolution of renal dysfunction (3,8,11,12,21,22,24,26). Considering the results reported by Yao et al (30) showing that an increase in COX2 may be secondary to an activation of neuronal nitric oxide synthase (nNOS), we also tested the hypothesis that the increments in COX2 elicited by HPI are accompanied by a simultaneous increment in nNOS. Studies to examine whether the previously mentioned hypotheses are correct have been performed in 3-to 4-and 10-to 11-mo-old rats treated with an AT 1 receptor antagonist (ARA) during the nephrogenic period (ARAnp).…”
mentioning
confidence: 91%
“…It was also expected that HPI-induced renal changes are greater in males than in females. These hypotheses are based on studies showing that HPI induces an increase in COX2 (30) and accelerates the progression of renal disease in several models of renal disease (6). It has also been reported that there are important sex-dependent differences in the evolution of renal dysfunction (3,8,11,12,21,22,24,26).…”
mentioning
confidence: 99%